Age And Fasting Blood Sugar Levels Are Associated Factors For Mindful Eating Among Type 2 Diabetes Mellitus Patients During Covid-19 Pandemic Confinement - Nurul Hayati Chamhuri; Noorlaili Mohd Tohit; Amirah Azzeri; Norshamliza Chamhuri; Siti Rohani M. Alias (PLOS ONE, 2024)
Indexed by Scopus/ERA